Maximizing Finance for Development in Agriculture and Food Systems in Ethiopia : An Analysis of Beef, Coffee, and Maize - World Bank (World Bank, Washington, DC, 2019)
The World Bank Group has developed a new diagnostic approach called Maximizing Finance for Development (MFD). This study pilots the use of the World Bank’s MFD approach to identify areas along value chains (VCs) where the private sector is involved. More important may be the identification of where the private sector is currently not involved or only involved peripherially. The results provide a range of opportunities to consider, with the purpose of crowding in more private sector investment and sustainable solutions to achieve the Sustainable Development Goals and meet the highest environmental, social, and fiscal responsibility standards. Under each function, the underlying causes of market failure are assessed, helping inform a range of possible opportunities for private sector to participation. The ouputs of this report can be used for further stakeholder engagement to prioritize issues and assess solutions. The focus is on the three VCs of beef, coffee, and maize. These commodities account for over 50 percent of Agricultural GDP and over 80 percent of foreign exchange revenue for the country and possess the potential for greater development impact through enhanced private sector activity. The nature of these commodities differs in terms of commercialization. Coffee, a pure cash crop, has close to 95 percent of its product sold by the farmer. In contrast, maize is primarily a food crop and 89 percent of maize produced is consumed by farming households. Cattle, on the other hand, are sold by pastoralists when cash is needed, cattle are no longer serve a productive purpose or meeting social obligations. In highland areas, the commercialization aspect of cattle is much greater. This has implications for private sector engagement in the respective value chains. This report identifies the issues and constraints in these three selected VCs and suggests opportunities for: (a) the public sector to amend policy, regulations, and provide inducements for greater private sector activity; and (b) the private sector to take on a greater level of responsible agricultural investment aligned with global good practice.